2022
DOI: 10.1186/s12245-022-00418-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiopulmonary resuscitation duration on the neurological outcomes of out-of-hospital cardiac arrest

Abstract: Background Patients experiencing cardiac arrest outside medical facilities are at greater risk of death and might have negative neurological outcomes. Cardiopulmonary resuscitation duration affects neurological outcomes of such patients, which suggests that duration of CPR may be vital to patient outcomes. Objectives The study aims to evaluate the impact of cardiopulmonary resuscitation duration on neurological outcome of patients who have suffered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…Various studies show that the duration of CPR is related to the return of spontaneous circulation, that the greatest benefits of CPR can be obtained in the first 10−15 min, and that increasing the duration of CPR will bring minimal benefits, with the average duration of CPR in patients who had successful CPR being less than 30 min 32 . According to Albinali et al, the average duration of CPR in patients who survived was 26.5 min, which is similar to the current study 33 . Receiving a defibrillator had a statistically significant relationship with the outcome of CPR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Various studies show that the duration of CPR is related to the return of spontaneous circulation, that the greatest benefits of CPR can be obtained in the first 10−15 min, and that increasing the duration of CPR will bring minimal benefits, with the average duration of CPR in patients who had successful CPR being less than 30 min 32 . According to Albinali et al, the average duration of CPR in patients who survived was 26.5 min, which is similar to the current study 33 . Receiving a defibrillator had a statistically significant relationship with the outcome of CPR.…”
Section: Discussionsupporting
confidence: 88%
“…32 According to Albinali et al, the average duration of CPR in patients who survived was 26.5 min, which is similar to the current study. 33 Receiving a defibrillator had a statistically significant relationship with the outcome of CPR. 37.5% of VT patients who received a defibrillator returned to their cardiac rhythm and had a successful resuscitation, while 27.6% of Vf patients who received a defibrillator had a successful resuscitation.…”
Section: Discussionmentioning
confidence: 96%
“…While this study emphasizes the role of initial rhythm, other patient-related factors playing a role in neurological outcomes despite prolonged CPR, it is similar to our study in the fact that they also report that total CPR duration was inversely associated with a CPC of 1-2 at discharge. According to another study conducted in Saudi Arabia by Albnali et al, patient-related characteristics such as age and preexisting medical comorbidities were much more important than CPR time in determining the neurological outcome [16]. Despite these factors playing a role, they also report that shorter duration of CPR was associated with favorable neurological outcomes, as seen in our study.…”
Section: Discussionsupporting
confidence: 66%
“…CPR is a lifesaving technique that combines chest compressions and rescue breaths to maintain circulation and oxygenation when the heart stops beating [ 33 ]. The duration of CPR plays a crucial role in determining the likelihood of a successful outcome in cardiac arrest patients [ 34 ]. Research has consistently demonstrated that shorter CPR duration is associated with higher survival rates and more favorable neurological outcomes [ 10 , 11 , 35 ].…”
Section: Discussionmentioning
confidence: 99%